Respuesta :

Answer:

Step-by-step explanation:

The distance between a point (x,y) and the point (-3,4) is

d1= [tex]\sqrt{ (x+3)2+(y-4)2}[/tex] .

The distance between a point (x,y) and the point (0,0) is

d2= [tex]\sqrt{x2+y2}[/tex] .

You know what y is from the equation of the line, so substitute that, set d1=d2, and solve for x.

The coordinates of the point on the straight line y=3x+1 that is equidistant from the origin and (−3, 4) is (-33/18, 39/6)

The distance formula is expressed as:

[tex]D=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\[/tex]

For the coordinate point (x,y) to (-3, 4), the distance is expressed as:

[tex]D_1 = \sqrt{(x+3)^2+(y-4)^2}\\[/tex]

For the coordinate point (x,y) to (0, 0), the distance is expressed as:

[tex]D_2=\sqrt{(x-0)^2+(y-0)^2}\\D_2 = \sqrt{x^2+y^2}[/tex]

Since the distance are equidistant, then D1 = D2

[tex]\sqrt{(x+3)^2+(y-4)^2} = \sqrt{x^2+y^2}\\ (x+3)^2+(y-4)^2 = x^2+y^2\\x^2+6x+9+y^2-8y+16 = x^2+y^2\\6x+9-8y+16=0\\6x-8y+25=0[/tex]

Substitute y = 3x+1 and get x

6x - 8y + 25 = 0

6x-8(3x+1) - 25 = 0

6x -24x-8-25=0

-18x-33 = 0

-18x = 33

x =-33/18

Sincey= 3x + 1

y = 3(33/18) + 1

y = 33/6 + 1

y = 39/6

Hence the required coordinates is (-33/18, 39/6)

Learn more here:https://brainly.com/question/7245260